Growth behaviors of platinum-assisted GaN nanostructures in vapor–liquid–solid mechanism. (November 2015) - Tan, L.K.; Yam, F.K.; Hassan, Z.
Abstract: This article reports the investigation of the growth behaviors of platinum-catalyzed GaN nanostructures grown via chemical vapor deposition method by manipulating growth temperature and ammonia flow rate. Morphological observation revealed the tapering behavior of GaN nanostructures at high growth temperatures and high ammonia flow rates in which the GaN nanowires were observed to be grown from the surface of GaN microcrystal structures. Growth mechanism of the tapering effect was discussed. X-ray diffraction showed the synthesized GaN nanostructures are of wurzite structure with no existence of impurities and found that GaN nanostructures grown at 1050 °C under ammonia flow rate of 250 sccm possessed the highest degree of crystallinity. Raman measurement exhibited no peak shift in E2 (high) while a redshift in A1 (LO) mode with rising growth temperatures, indicating the decreased of carrier concentration in the GaN nanostructures.